2018
DOI: 10.1103/physrevc.97.055801
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of Ar38+α reaction cross sections relevant to the Ca41 abundance in the solar system

Abstract: In massive stars, the 41 Ca(n, α) 38 Ar and 41 K(p, α) 38 Ar reactions have been identified as the key reactions governing the abundance of 41 Ca, which is considered as a potential chronometer for Solar-System formation. So far, due to experimental limitations, the 41 Ca(n, α) 38 Ar reaction rate is solely based on statistical model calculations. In the present study, we have measured the time-inverse 38 Ar(α, n) 41 Ca and 38 Ar(α, p) 41 K reactions using an active target detector. The reactions were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
(138 reference statements)
1
9
0
Order By: Relevance
“…Of course, such a statistical model approach can only be valid on average, and individual resonances in the 13 C(α,n) 16 O reaction may show a completely different decay branching. But it has been shown recently that a careful selection of TALYS parameters allows to reproduce (α,n) cross sections for intermediate [20,21] and even light nuclei [22], at least at energies E α above a few MeV. The calculated branching ratios b j as a function of energy E α are shown in Fig.…”
Section: Re-analysis Of the Har05 Datamentioning
confidence: 99%
“…Of course, such a statistical model approach can only be valid on average, and individual resonances in the 13 C(α,n) 16 O reaction may show a completely different decay branching. But it has been shown recently that a careful selection of TALYS parameters allows to reproduce (α,n) cross sections for intermediate [20,21] and even light nuclei [22], at least at energies E α above a few MeV. The calculated branching ratios b j as a function of energy E α are shown in Fig.…”
Section: Re-analysis Of the Har05 Datamentioning
confidence: 99%
“…For this purpose the TALYS code (version 1.9) [54] was used which is a well-established open-source code for SM calculations. Similar to previous studies (see [55] for 64 Zn + α, [56,57] for 38 Ar + α and [23] for 115 In + α), the complete TALYS parameter space was investigated, and a χ 2 -based assessment was used to find the best description of the experimental data. In practice, 14 different A-OMPs were used which turn out to be the most important ingredient of the SM calculation.…”
Section: χ 2 -Based Assessmentmentioning
confidence: 99%
“…There have been a few experimental studies using 17 F beams [20][21][22]. One such study measured the fusion cross section for a 208 Pb target where it was concluded that at energies around the Coulomb barrier no enhancement of the fusion cross section is observed [9], in contrast with the results for the 8 B + 58 Ni system [17] but consistent with those for 8 B + 28 Si [18]. It has been suggested that this lack of an enhancement in the fusion cross section could be due to an effective polarization of the 17 F in the strong Coulomb field of the 208 Pb target, leading to a shielding effect on the halo proton [23].…”
Section: Introductionmentioning
confidence: 82%
“…Details of the Encore detector will be published in a separate paper [26]. This detector system and analysis procedure has been successfully used at ANL for measurements of fusion reactions with carbon isotopes [3] as well as for measurements of (α,p) and (α,n) reactions [27,28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation